2020
DOI: 10.1097/01.aog.0000663268.02488.79
|View full text |Cite
|
Sign up to set email alerts
|

Examining Joint Effect of Race and Neighborhood Socioeconomic Disadvantage on Adverse Obstetric Outcomes [09C]

Abstract: INTRODUCTION: The Area Deprivation Index (ADI) is a neighborhood-level index derived from census data to capture spatial socioeconomic status (SES). The primary objective was to assess the joint relationship between race/ethnicity and neighborhood disadvantage on obstetric outcomes at a single Midwestern- academic institution, situated in a city with high economic-segregation. METHODS: A retrospective cohort study of births at a single academic institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These results are similar to other studies demonstrating stronger predictive relationships between ADI and poor health outcomes among White patients compared to Black patients. [ 22 , 32 , 33 ] Living in a deprived community exposes an individual resident, regardless of their race or ethnicity, to the cumulative effects of area poverty and subsequently impacts health outcomes. 34 However, for racial/ethnic minority patients, the lack of association of outcomes in the present study with ADI suggests that there are likely additional unmeasured social determinants of health that are based in structural racism and inequality that contribute to the observed disparity in hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to other studies demonstrating stronger predictive relationships between ADI and poor health outcomes among White patients compared to Black patients. [ 22 , 32 , 33 ] Living in a deprived community exposes an individual resident, regardless of their race or ethnicity, to the cumulative effects of area poverty and subsequently impacts health outcomes. 34 However, for racial/ethnic minority patients, the lack of association of outcomes in the present study with ADI suggests that there are likely additional unmeasured social determinants of health that are based in structural racism and inequality that contribute to the observed disparity in hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have attempted to understand the complex and layered relationship between race/ethnicity, socioeconomic status, and prenatal care outcomes have demonstrated that racial disparities may be context dependent. Although higher SES can have a protective effect on maternal and infant outcomes, whether it eliminates racial disparities seen in outcomes depends on the care context [10,11]. One study looking at the interaction effects of race, SES, and neighborhood on infant birthweight found that the gap in lower birthweight between infants born to Black and White women was moderately reduced when both were of similar SES and living in racially concordant neighborhoods; on the contrary, higher SES Black women living in disproportionately White neighborhoods had the worst outcomes in infant birthweight [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has long been suspected and recently documented that racism, including structural racism, is a likely contributor to the widening disparity in maternal health outcomes between White and Black women [7,[10][11][12][13][14]. One way in which structural racism is observed in healthcare is through the overrepresentation of residency clinics in predominantly underserved communities made up of non-White racial or ethnic groups minorities [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In parallel, growing evidence shows that neighborhood-level disadvantage has detrimental impacts on women's health more generally, possibly through health-related behaviors, resource availability, and environmental toxicants. [21][22][23][24] These same exposures have implications for women's reproductive health, 25 yet few studies have explored links between neighborhood-level SES and ovarian reserve specifically. One prior study showed that lower neighborhood-level SES among mothers was associated with lower ovarian reserve in their adult daughters, 26 indicating that SES-related exposures in utero may influence the size or health of offspring ovarian reserve.…”
mentioning
confidence: 99%